2017
DOI: 10.1186/s12991-017-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and antidepressants pharmacokinetics: a systematic review

Abstract: BackgroundDespite an increasingly recognized relationship between depression and smoking, little is known about how smoking influences antidepressant response and treatment outcomes. The aim of this study was to systematically review the evidence of the impact of smoking on new-generation antidepressants with an emphasis on the pharmacokinetic perspective.MethodsWe present a systematic review of clinical trials comparing the serum levels of new-generation antidepressants in smokers and nonsmokers. Data were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Our study showed that pyrilamine exhibited competitive inhibition of [ 3 H]nicotine uptake with a K i of 15 µM (Fig. 3B), whose value was similar to the K m value in pyrilamine uptake (28 µM), 45) suggesting that nicotine and pyrilamine share the same transport system, which is known as the H + /organic cation antiporter.…”
Section: Influx and Efflux Transport Of Nico-tine Across The Bbbsupporting
confidence: 67%
See 1 more Smart Citation
“…Our study showed that pyrilamine exhibited competitive inhibition of [ 3 H]nicotine uptake with a K i of 15 µM (Fig. 3B), whose value was similar to the K m value in pyrilamine uptake (28 µM), 45) suggesting that nicotine and pyrilamine share the same transport system, which is known as the H + /organic cation antiporter.…”
Section: Influx and Efflux Transport Of Nico-tine Across The Bbbsupporting
confidence: 67%
“…Yamazaki et al 44) reported that pyrilamine is transported to the brain across the BBB via carrier-mediated transport system. In addition, Okura et al 45) revealed the involvement of novel H + /organic cation antiporter Figure 3B was adapted from Tega Y, Akanuma S, Kubo Y, Terasaki T, Hosoya K. Blood-to-brain influx transport of nicotine at the rat blood-brain barrier: Involvement of a pyrilaminesensitive organic cation transport process. Neurochem.…”
Section: Influx and Efflux Transport Of Nico-tine Across The Bbbmentioning
confidence: 99%
“…The therapy choice should be based on the status of the patientwhether he is a smoker or non-smoker, due to the risk of pharmacokinetics interactions. 52 Alcohol consumption is also contraindicated during the therapy with antidepressants. The pharmacist should clarify that antidepressants might lead to drowsiness and disturbances in concentration and therefore may influence the ability to drive and use machines.…”
Section: Identification and Prevention Of Drug-related Problemsmentioning
confidence: 99%
“…Smoking, SMI medications and COVID-19. among people with SMi, smoking is likely to interact with factors modulating vulnerability to coVid-19, such as the use of psychotropic medications and maintenance of an unhealthy dietary pattern (98)(99)(100)(101). For instance, smoking has been shown to increase the clearance of specific antipsychotics, namely clozapine and olanzapine, and antidepressants, namely fluvoxamine, duloxetine, mirtazapine and trazodone, by inducing their metabolism in the liver, suggesting that smokers may be at risk of undertreatment (98,101).…”
Section: Cigarette Smoking As a Possible Modulator Of Covid-19 Severity Among Patients With Smimentioning
confidence: 99%